The Role of Drug Swallowing Supervisors (PMO) in Improving Tuberculosis Treatment Adherence: A Literature Review - Huda, Nurul; Cahyono, Bagus Dwi; Aristawati, Evy; Salamah, Saidatus; Ainiyah, Nur (Al-Hijrah Indonesia, 2024)
Tuberculosis (TB) is an infectious disease caused by the bacterium Mycobacterium tuberculosis, which can attack all organs, especially the lungs. Tuberculosis remains the world's deadliest infectious disease, with more than 9 million infections and 1.7 million deaths per year. If not treated or managed correctly, this disease can lead to serious consequences and even death. The purpose of this literature review is to obtain an overview of the relationship between drug-taking supervisors (PMO) and the level of adherence to treatment visits in pulmonary TB patients from various perspectives and various similar studies. The research method used in this study is a literature review, which includes an analysis of 8 articles obtained from three databases: ProQuest, Science Direct, and Google Scholar. The search keywords used for article retrieval included